Intervenção social em casas de acolhimento residencial em tempos de pandemia: https://doi.org/10.53809/TS_ISS_2023_n.4_68-78 ("Temas Sociais" Journal, 2023)
The COVID-19 pandemic brought issues that challenged social intervention. This study aimed to investigate the challenges imposed on the dynamics of Residential Care Homes (RCH) during the pandemic. The sample included 27 participants: two technical directors, two social workers, two psychologists, four kindergarten teachers, and seventeen education assistants. Through the qualitative methodology, with the techniques of semi-structured interviews and content analysis, it was found that the biggest challenge is the management of children in the CAR space. At the level of the children's functioning dynamics, there was greater instability. Sanitization and the use of technology stood out in the practices used in the RCH.